Thermal Performance Improvement of the Heat Pipe by Employing Dolomite/Ethylene Glycol Nanofluid - Duygu Yilmaz Aydin; Metin Gürü; Adnan Sözen; Erdem Çiftçi (International Journal of Renewable Energy Development, 2020)
In heat transfer applications, heat pipes are widely- preferred because of some characteristics such as low cost, being able to be produced in any size and low maintenance cost make them superior. Moreover, the working fluid to be employed substantially affects the heat transfer characteristics of a heat pipe. In this paper, effects of nanoparticle addition into the ethylene glycol on heat pipe’s thermal performance were analysed experimentally. Every test was done using two variant working fluids, ethylene glycol and dolomite nanoparticles-doped ethylene glycol, respectively. Dolomite nanoparticles (2% by weight) and Sodium Dodecyl Benzene Sulfonate (0.5% by weight) were doped into the ethylene glycol while preparing the dolomite/ethylene glycol nanofluid. After filling in the heat pipe, experiments were realized under changing working conditions. Using experimental data, efficiency and thermal resistance of the heat pipe were examined. Viscosity of the each working fluid was determined. The contact angle –wettability measurements were also performed to specify the effects of surface active agent addition. The obtained findings revealed that nanoparticle inclusion inside the base fluid, i.e. ethylene glycol, improved the thermal performance (efficiency) and decreased the heat pipe’s thermal resistance substantially. ©2020. CBIORE-IJRED. All rights reserved